Effectiveness of Services at Bank Sumut KCP Syariah Rantauprapat - Rahmad Raihan Munthe (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the effectiveness of the services provided by Bank Sumut Syariah in meeting customer needs for sharia banking services. This research uses a descriptive qualitative approach by collecting data through interviews with banks, customers and employees such as tellers and customer service. The research results show that Bank Sumut Syariah's services are classified as effective in several aspects such as transparency of information, friendliness of officers, and ease of access to services. However, there are still several obstacles such as limited digital service features and lack of delivery of promotional information that need to be improved so that services are more optimal. Apart from that, customers also face various technical obstacles such as frequent disruptions to mobile banking services, system delays during digital transactions, and suboptimal ATM availability. This shows the need for improvements in technological infrastructure and more effective service communication strategies in the future. This research also highlights the importance of ongoing officer training and efforts to expand education to the public to understand the advantages of sharia-based services.